Standard, Reputation and Trade: Evidence from US horticultural imports refusals - Marie-Agnès Jouanjean (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
This paper investigates the impact of food safety standards promulgated by governments or imposed by byers from the private sector on the capacity of developing countries to access developed countries' markets for high value agricultural and food products. I offer an analysis that disentangles productivity-sorting from quality-sorting in fresh fruits and vegetables exports. My theoretical model and empirical analysis confirms the importance of taking into consideration importers' preference for quality as well as exporters' capacity to produce quality products when analyzing average export unit prices of fresh fruits and vegetables. Thanks to a new database on U.S import refusals, my empirical analysis shows that a shock to reputation seems to have a downgrading effect, reducing the capacity of countries to export quality products.
Keywords: F13; O13; Q17; 330; SPS; agricultural trade; quality sorting; reputation